2014
DOI: 10.1088/0953-8984/27/2/025401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electronic energy loss in graphene and BN sheet by means of time-dependent density functional theory

Abstract: Time-dependent density functional theory combined with Ehrenfest dynamics are employed to calculate electronic energy loss of energetic ions in two-dimensional graphene and white graphene (BN) targets. Special attention is paid to the effects of different electronic structures on their stopping power. Our results show that the energy transferred to the graphene target is much larger than to BN for both H(+) and He(2+) projectiles. Since the energy is mainly deposited into the electronic degree of freedom, it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 27 publications
7
64
0
Order By: Relevance
“…We have shown that the centroid path approximation [36,37] accurately reproduces electronic stopping power values of the ensemble average, while the agreement is worse for the velocities near the stopping power maximum. We have also quantified the velocity-dependent mean steady-state charges for protons and α-particles in SiC to examine the extent to which a linear response treatment can be applied.…”
Section: Discussionmentioning
confidence: 94%
“…We have shown that the centroid path approximation [36,37] accurately reproduces electronic stopping power values of the ensemble average, while the agreement is worse for the velocities near the stopping power maximum. We have also quantified the velocity-dependent mean steady-state charges for protons and α-particles in SiC to examine the extent to which a linear response treatment can be applied.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, in this Letter we predict a novel mechanism to induce and control the formation of doublons in a finite system where the excitation is localized in space and time and driven by energetic ions penetrating a strongly correlated material and depositing energy ("stopping power", e.g. [19][20][21]). The mechanism is demonstrated by exact diagonalization simulations, and a physical explanation is given with an analytical model in terms of the Landau-Zener effect [22].…”
mentioning
confidence: 89%
“…Quantum transitions inside the projectile and charge transfer have been studied approximately with quantum kinetic models (Newns‐Anderson model) where the projectile was treated as a few level system . Furthermore, there have been a number of TDDFT studies of ions impinging onto correlated materials such as graphene or boron nitride (BN) and on finite systems such as metal clusters, carbon nanostructures, or graphene fragments (for more references see ref. ), where quantum transitions inside the projectile are taken into account.…”
Section: Embedding Scheme To Capture Charge Transfer Dynamics Betweenmentioning
confidence: 99%